A Meta-Analysis of Preterm Infant Massage: An Ancient Practice With Contemporary Applications. Issue 6 (November 2015) - Unknown
Abstract: Objective: To evaluate the efficacy of massage on the short- and long-term outcomes of preterm infants. Methods: A search was conducted using the PRISMA framework. Validity of included studies was assessed using criteria defined by the Cochrane Collaboration that was carried out independently by two reviewers with a third reviewer to resolve differences. Results: Thirty-four studies met the inclusion criteria, 3 were quasi-experimental, 1 was a pilot study, and the remaining 30 were randomized controlled trials (RCTs). The outcomes that could be used in the meta-analysis and found in more than three studies noted that massage improved daily weight gain by 0.53 g (95% CI = 0.28-0.78), p < 0.0001, and resulted in a significant improvement in mental scores by 7.89 points (95% CI = 0.96-14.82), p < 0.03. There were no significant effects on length of hospital stay, caloric intake, or weight at discharge. Other outcomes were not analyzed either because the units of measurement varied or because means and standard deviations were not provided by the authors. These included vagal activity and heart rate variability (5 studies), neurobehavioral states (7 studies), pain responses (2 studies), maternal outcomes (2 studies), breastfeeding (2 studies), and physiologic parameters: bone formation (2 studies), immunologic markers (1 study), brain maturity (1 study), and temperature (1 study). The quality of the studies was variable with methods of randomization and blinding of assessment unclear in 18 of the 34 studies. Conclusions: Massage therapy could be a comforting measure for infants in the NICU to improve weight gain and enhance mental development. However, the high heterogeneity, the weak quality in some studies, and the lack of a scientific association between massage and developmental outcomes preclude making definite recommendations and highlight the need for further RCTs to contribute to the existing body of knowledge. Abstract : Massage therapy may be a comforting measure for infants in the neonatal intensive care unit (NICU) to improve weight gain and enhance mental development. However, based on the state of the current evidence, it is challenging to make definite clinical recommendations.